On the Throughput of Feedbackless Segmented Network Coding in Delay Tolerant Networks - Li, Zhuo; Zeng, Deze; Guo, Song; Lu, Sanglu; Chen, Daoxu; Zhuang, Weihua (IEEE Wireless Communications Letters, 2012)
Epidemic routing using random linear network coding has been studied and proved as an efficient way for light data delivery in delay tolerant networks (DTNs). In this paper, we study bulk or stream-like data dissemination in DTNs. Segmented network coding is introduced to provide best-effort services and its performance in terms of sustained throughput is analyzed. To our best knowledge, we are the first to give the closed-form expression of the maximum sustained throughput using feedbackless segmented network coding in DTNs. A protocol is also proposed and simulation results show that it approaches the theoretical bound asymptotically.